Transapical combined transcatheter aortic valve-in-valve implant and ascending aorta endovascular repair. (24th January 2022) - Agostinelli, Andrea; Gallingani, Alan; Borrello, Bruno; Nicolini, Francesco
Abstract: We report the case of a 64-year-old patient who previously had an aortic valve replacement with a stentless aortic valve and an ascending aorta replacement for a DeBakey type II aortic dissection. The patient was referred to us for symptomatic aortic regurgitation related to bioprosthesis degeneration and a pseudoaneurysm at the distal anastomotic site of the vascular graft. Due to the presence of several comorbidities, the patient had a combined transapical transcatheter aortic valve-in-valve implant and an ascending aorta endovascular repair. Abstract : A transapical transcatheter aortic valve implant (TAVI) is a well-established alternative approach to the treatment of an aortic valve in patients with unsuitable peripheral access [1].